Does adoption of climate change adaptation strategy improve food security? A case of rice farmers in Ogun State, Nigeria - Ojo, Temitope Oluwaseun; Ogundeji, Abiodun A.; Emenike, Chijioke U. (MDPI, 2022)
The southwestern part of Nigeria, particularly Ogun State, is more vulnerable to the vagaries of climate change due to the high dependence on rain-fed agriculture and limited capacities to respond to climate change. In this study, factors influencing climate change adaptation strategies and its impacts on household food security of smallholder rice farmers in Ogun State were estimated. A multistage sampling technique was employed to select 120 smallholder rice farmers in the study area. The factors influencing the adoption of climate change adaptation practices and their impacts on household food security among smallholder rice farmers in Ogun State were examined using a probit model and an endogenous switching probit model (ESPM). According to the results of household dietary diversity score (HDDS), adopters of climate change adaptation techniques have higher levels of food security than non-adopters. The outcome of the ESPM shows that access to market information, access to extension agents, gender, off-farm income, and membership in cooperatives all contribute to the variations in food security experienced by both adopters and non-adopters of climate change adaptation strategies. A unit increase in adoption of climate change adaptation measures will increase household food security by about 3 units while decreasing severity in food insecurity by about 3.2 units. Therefore, it is recommended that policies that would support smallholder farmers’ decisions to embrace measures for coping with climate change should be encouraged in order to stimulate their adaptive capacity. Additionally, in order to secure the inclusive sustainability of the agricultural sector, stakeholders and NGOs must collaborate with each other to enhance the circumstances under which farmers may receive climate change information, timely agricultural loans, and policy incentives.
Keywords: Rice; HDDS; Climate change; Adaptation strategies; ESPM; AIPW